A COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE BETWEEN STATE-OWNED ENTERPRISES AND STATE-OWNED ENTERPRISES THAT HAVE GONE PUBLIC: A CASE STUDY OF 7 INDONESIAN COMPANIES AMONG THE WORLD’S 2,000 LARGEST COMPANIES - Vivi Sukma Puspa Dewi; Abang Firdaus; Yayan Cahyana; Deden Rizal Riadi (PT. Altin Riset Publishing, 2026)
This study aims to analyze and compare the financial performance of Indonesian state- owned enterprises (BUMN) and privately-owned public companies (BUMS) listed among the 2000 largest companies in the world. The analysis employs four financial performance indicators: Operating Efficiency, Economic Value Added (EVA), Financial Value Added (FVA), and Market Value Added (MVA) over the period 2013–2024. This research uses a quantitative descriptive approach with purposive sampling, involving several companies. The hypothesis testing was conducted using the non-parametric Mann-Whitney test. The results show that there is no significant difference in Operating Efficiency between BUMN and BUMS, indicating that both groups have relatively similar operational efficiency. In contrast, the EVA variable shows a significant difference between the two groups. The FVA results also indicate a significant difference, as does the MVA variable. These findings suggest that while operational efficiency is relatively equal, BUMS outperform BUMN in generating economic, financial, and market value.